Analisis Faktor-Faktor Kemasan (Packaging) dalam Mempengaruhi Keputusan Pembelian Oleh-Oleh Makanan Khas Tanjungpinang - Iranita Iranita (Bahtera Inovasi, 2020)
The increasing likelihood of community buying today is on the food sector. Along with that, especially the growth of the business shop souvenirs typical of Tanjungpinang which is a part of culinary tourism for local people or tourists both from domestic and foreign. One important factor of packaging for the success of a product, then in this case marketers demanded more innovative and creative so that it can attract consumers in influencing consumers to provide a positive response and minimize negative risk of post-consumption. The purpose of this research is to know the role of packaging factor in influencing the decision of purchasing souvenirs from Tanjungpinang. This research is explanatory research using factor analysis. In this study the number of variables set is 9 variables that relate to the packaging factor packaging in influencing the decision of the purchase of souvenirs typical of Tanjungpinang. The results of this research are the product factors, security, economics, distribution channels, communication, ergonomic, aesthetics, identity, promotion, and environment are factors that influence the decision of the purchase of souvenirs typical of Tanjungpinang